Reconstructing the Hadiths on the Obligation of Hajj: A Study of ʿIlal and Visa Quota Policies from the Perspective of Uṣūl al-Fiqh - Ali Yusuf Muzaki; Zakaria; Muhammad Syafiiq; Ridwan; Ahmad 'ubaydi hasbillah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This article aims to reconstruct the understanding of hadiths on the obligation of Hajj through the approaches of ʿilal al-Ḥadīth, and to analyse their implications for quota and visa regulations in the perspective of uṣūl al-fiqh. The hadiths concerning the obligation of Hajj essentially affirm a universal command for every Muslim who possesses the required capability (istiṭāʿah) to perform it once in a lifetime. However, in the contemporary context, the performance of Hajj faces various administrative regulations, such as quota restrictions imposed by the Saudi Arabian government and the requirement of visas as formal legal instruments. This study employs an integrative-qualitative design using both library research and field research, and applies three levels of analysis: fiqh al-Ḥadīth, ʿilal al-Ḥadīth, and naqd al-matn, alongside the uṣūl al-fiqh perspective related to taqyīd al-mubāḥ, maṣlaḥah mursalah, and the concept of istiṭāʿah. The findings indicate that quota and visa regulations do not contradict the substance of the hadiths on the obligation of Hajj; rather, they constitute a form of legal contextualisation aimed at safeguarding public interest, order, and the safety of pilgrims. Accordingly, the understanding of hadiths on the obligation of Hajj needs to be dynamically reconstructed so that it remains relevant to social realities and modern policy frameworks, without neglecting the authority of the hadith texts and the foundational principles of uṣūl al-fiqh.